The level of psychological stress and its relationship to some variables among female students of the Faculty of Education at the University of Hail - Al-Hamdhawi, Alaa Falah (Journal of Educational and Psychological Sciences, 2024)
This study aimed to identify the level of psychological stress and its relationship to some variables among female students of the Faculty of Education at the University of Hail; to uncover differences between female students in the psychological stress due to variables Scientific specialization, housing, academic achievement. The researcher used the descriptive method. The researcher applied the following tool: A measure of psychological stress divided into six axes (Social, financial, academic, personal, health, and future). It was applied to a sample of (434) female students. The results of the study indicated that female students have psychological stress with a medium degree. There were statistically significant differences at the level of α≤0.05 in the responses of the sample of the study about the social stress due to the difference in Scientific specialization and the differences in favor of the physical education group. There were statistically significant differences at the level of α≤0.05 in the responses of the sample of the study about the Social, financial, and personal stress due to the difference in housing and the differences in favor of the living alone group. There were statistically significant differences at the level of α≤0.05 in the responses of the sample of the study about the Social and future stress due to the difference in academic achievement and the differences in favor of (Good) and (Acceptable) group. The study also concluded that psychological counseling programs were designed to enhance psychological security among female students.
Keywords: Psychological stress; female students of the faculty of Education; University of Hail